2017
DOI: 10.3847/1538-4357/aa7890
|View full text |Cite
|
Sign up to set email alerts
|

Role of Surface Chemistry in Grain Adhesion and Dissipation during Collisions of Silica Nanograins

Abstract: The accretion of dust grains to form larger objects, including planetesimals, is a central problem in planetary science. It is generally thought that weak van der Waals interactions play a role in accretion at small scales where gravitational attraction is negligible. However, it is likely that in many instances, chemical reactions also play an important role, and the particular chemical environment on the surface could determine the outcomes of dust grain collisions. Using atomic-scale simulations of collisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Experimental silanol densities are in the range of 2.6-4.6 OH nm −2 [24]. Other simulation studies gave lower values, 2.0-2.5 OH/nm 2 [25,27] or even only 1.3-1.8 OH/nm 2 [19], but also higher values of 6.6 OH/nm 2 [26,28]. This large variety is due to (i) possibly incomplete identification of under-coordinated surface atoms and (ii) atomic surface roughness resulting in a larger effective surface area than the calculated area [26,28].…”
Section: Methodsmentioning
confidence: 88%
See 4 more Smart Citations
“…Experimental silanol densities are in the range of 2.6-4.6 OH nm −2 [24]. Other simulation studies gave lower values, 2.0-2.5 OH/nm 2 [25,27] or even only 1.3-1.8 OH/nm 2 [19], but also higher values of 6.6 OH/nm 2 [26,28]. This large variety is due to (i) possibly incomplete identification of under-coordinated surface atoms and (ii) atomic surface roughness resulting in a larger effective surface area than the calculated area [26,28].…”
Section: Methodsmentioning
confidence: 88%
“…Quadery et al [19] simulated nanometer-sized hydroxylated a-SiO 2 NPs (radii of 1 and 2 nm) with the REAX potential and demonstrated that such NPs exhibit reduced adhesion. They report bouncing velocities of around 0.6 and 0.3 km/s for R = 1 and 2 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations